2021
DOI: 10.1016/j.trechm.2020.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Large-Area Single-Crystal Graphene

Abstract: There have been breakthroughs in the mass production of graphene by chemical vapor deposition (CVD) and its practical applications have also been identified. Grain boundaries are typically present in 'CVD graphene' and adversely impact its properties. We summarize recent progress in growing large-area singlecrystal graphene. Centimeter-scale single-crystal, truly single-layer graphene (SLG) films have been reportedly achieved on single-crystal Cu(111) foils by CVD growth, while meter-scale single-crystal SLG f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 118 publications
0
24
0
Order By: Relevance
“…The epitaxial growth of single crystal graphene on a single crystal metal substrate, especially a single crystal Cu(111) foil, has been reported. [ 15,29–32 ] Since both graphene and the Cu substrate are single crystals, the influence by defects and GBs in both graphene and Cu can be minimized, thus this single crystal graphene‐coated Cu(111) is a good platform to investigate whether it is possible to minimize or even eliminate oxidation of the Cu using graphene as a barrier. Xu et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epitaxial growth of single crystal graphene on a single crystal metal substrate, especially a single crystal Cu(111) foil, has been reported. [ 15,29–32 ] Since both graphene and the Cu substrate are single crystals, the influence by defects and GBs in both graphene and Cu can be minimized, thus this single crystal graphene‐coated Cu(111) is a good platform to investigate whether it is possible to minimize or even eliminate oxidation of the Cu using graphene as a barrier. Xu et al.…”
Section: Introductionmentioning
confidence: 99%
“…The epitaxial growth of single crystal graphene on a single crystal metal substrate, especially a single crystal Cu(111) foil, has been reported. [15,[29][30][31][32] Since both graphene and the Cu substrate are single crystals, the influence by defects and GBs in both graphene and Cu can be minimized, thus this single crystal graphene-coated Cu(111) is a good platform to investigate whether it is possible to minimize or even eliminate oxidation of the Cu using graphene as a barrier. Xu et al reported that asgrown single crystal graphene islands on a Cu(111) foil protect the Cu surface from wet-oxidation by preventing water and/or O 2 from diffusing to the graphene/Cu(111) interface when exposed to humid air (relative humidity > 80%) at 50 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Mass production schemes discussed in this section includes graphene transfer process using roll-to-roll (R2R) processing, graphene growth and MEMS device fabrication on transition metal thin films for transfer-free process, controlled graphene growth on single-crystalline films, strain engineering on the substrate, and other approaches. [183][184][185]. Two data points with asterisks represent CVD growth of graphene by accelerated growth technique [186,187].…”
Section: Proposed Solutionsmentioning
confidence: 99%
“…Cu (111) and graphene have 4% lattice mismatch, and as temperature is highly elevated during graphene growth, the domains connect with each other creating seamless boundaries. It has been reported merging of grain boundaries is critical to electrical quality of graphene as electron scattering is observed near grain boundaries and wrinkles [5,184,214]. [209].…”
Section: Substrate Engineering For Single-seed Growth For Single Crystal Graphene (Scg)mentioning
confidence: 99%
See 1 more Smart Citation